'Nurses whisper.' Identities in nurses' patient safety narratives of nurse‐trainee doctors' interactions. Issue 12 (23rd June 2021) - Samuriwo, Ray; Bullock, Alison; Webb, Katie; Monrouxe, Lynn V.
Abstract: Context: Nurses are integral to patient safety, but little is known about their narrative constructions of identity in relation to their dyadic interactions with trainee doctors about patient safety and competence during the trajectory of a medical career. Aim: We sought to examine how identities are constructed by experienced nurses in their narratives of patient safety encounters with trainee doctors. Methods: Our qualitative study gathered narrative data through semi‐structured interviews with nurses of different professional standing (n = 20). Purposive sampling was used to recruit the first eight participants, with the remainder recruited through theoretical sampling. Audio recordings were transcribed verbatim and analysed inductively through a social constructionist framework and deductively using a competence framework. Results: We classified seven identities that participants constructed in their narratives of dyadic interactions with trainee doctors in relation to patient safety: nurses as teacher, guardian of patient wellbeing, provider of emotional support, provider of general support, expert advisor, navigator and team player . These identities related to the two key roles of nurses as educators and as practitioners. As they narrated these dyadic interactions, participants constructed identities that positioned trainee doctors in character tropes, suggesting gaps in professional competence: nurses as provider of general support was commonly narrated in the context of perceived deficits of personal or functional capabilities and nurses as team player was mainly associated with concerns (or reassurances) around ethical capabilities. Discussion and Conclusion: Our findings are consistent with, and extend the wider literature on the development of professional competence, interprofessional collaboration in health care, and the nature and organisation of nursing work. Nurses' work in ensuring patient safety and support trainee doctors' professional development merits greater formal recognition and legitimation. Abstract : This study sheds new light on the identities experienced nurses construct in their narratives of interactions with trainee doctors, thus facilitating learning in practice about key tenets of medical competence.